2023
DOI: 10.3389/fmolb.2023.1153420
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model of membrane protrusions driven by curved active proteins

Abstract: Eukaryotic cells intrinsically change their shape, by changing the composition of their membrane and by restructuring their underlying cytoskeleton. We present here further studies and extensions of a minimal physical model, describing a closed vesicle with mobile curved membrane protein complexes. The cytoskeletal forces describe the protrusive force due to actin polymerization which is recruited to the membrane by the curved protein complexes. We characterize the phase diagrams of this model, as function of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It was recently found that a high concentration of curved proteins may induce protrusive forces and sheet-like lamellipodia on highly curved surfaces in order to minimize membrane free energy [33,34]. Theoretical considerations show that the redistribution of membrane proteins and active forces are closely connected to the membrane shape [35].…”
Section: Migration Of Cancer Cells: Why What How and Whenmentioning
confidence: 99%
“…It was recently found that a high concentration of curved proteins may induce protrusive forces and sheet-like lamellipodia on highly curved surfaces in order to minimize membrane free energy [33,34]. Theoretical considerations show that the redistribution of membrane proteins and active forces are closely connected to the membrane shape [35].…”
Section: Migration Of Cancer Cells: Why What How and Whenmentioning
confidence: 99%
“…Multimeric interactions between receptors can drive the formation of nanodomains in the plasma membrane ( 21 , 22 ). Topographical structures, such as protrusions, can also cause the segregation of receptors ( 23 25 ). The ability of membrane proteins to associate with cortical cytoskeleton may also affect the localization and clustering of receptors ( 24 , 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, curvature‐mediated pattern formation plays a role in the formation of cellular protrusions, such as those involved in cell migration or myelination‐like coiling. There, proteins such as curved BAR proteins couple to membrane shape and interact with the actin cytoskeleton, producing dynamic patterns and protrusions on the cell surface (Simunovic et al , 2015; Carman & Dominguez, 2018; Gov, 2018; Wu et al , 2018; Begemann et al , 2019; Sadhu et al , 2021, 2023; Ravid et al , 2023).…”
Section: Introductionmentioning
confidence: 99%